PENGEMBANGAN TEKNIK KULTIVASI Spirulina sp. SEBAGAI SUMBER BIOMASSA ENERGI TERBARUKAN DALAM FOTOBIOREAKTOR AIRLIFT - Fifin Hindarti; Endah Ayuningtyas (Jurnal Energi dan Lingkungan (Enerlink), 2020)
The development of technology for the use of natural resources as fuel is increasing. One of them is theresearch of third generation biodisel. This technology utilizes microalgae as an environmentallyfriendly raw material which is also a renewable energy source for oil. Biodiesel from microalgaeespecially Spirulina sp. is one of the energy sources that can replace conventional diesel fuel whichhas potential for high lipid content. This study aims to develop a microalgae cultivation technology in anairlift photobioreactor by adjusting the light intensity of the LED lamp to obtain an optimal growth rateand increase the biomass production of Spirulina sp. The research was conducted on an intermediatescale using an airlift type photobioreactor with varying light intensity, namely 1600 lux, 2200 lux, and3200 lux. Each treatment was carried out three times for 14 days. Measurement of biomass weight wascalculated using the gravimetric method, by taking samples every 7 days. Based on the data obtained,the application of different light intensities to the spirulina sp. cultivation system will have an effect onthe final result in harvesting day 14th, specifically the weight of the biomass produced. The averageyield of biomass on day 14th with the best results was obtained at light intensity of 1600 as much as 623mg / 100 ml.